The Outcomes of High Population and Rich Cultural Difference among the School Students in Metropolitan, Delhi - Gusain, Pradeep (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
It is very fascinating to explore the effect of high population and rich cultural differences in a Metropolitan city like Delhi. Delhi in the true sense is a mini-India, where the different sections of people live together in harmony. It is very important to explore whether a high population leads to a scarcity of resources or not. The cultural differences make the Delhi Classroom, a typical ground of experimentation not among the students but among the teachers as well as among other stakeholders from every corner of the world. The high student-teacher ratio as present across the world platform, poses several challenges to the teachers, which leads adaptation of special strategies to tackle the problem. The weakness arises due to various issues as a function of the high population is overcome by rich cultural differences present in Delhi city. The Delhi school classroom provides a role model to all the schools across India. How the people in Delhi celebrate festivals with each other and how these practices of societies are reflected in the classroom, is also a matter of great achievement. The classrooms in Delhi not only have differences in terms of social aspects but also in terms of the economic status of the students. Due to high population density, a rich social fabric helps the students to build up their personality in terms of true Indian Citizens. The celebration of festivals of different communities in society by the parents as well as by the students among their friends helps to build a strong bonding among different sections of society. The cultural difference which arises as a result of the high population in Delhi, also helps the teachers to understand the culture of other states and this helps them to shape their teaching methodology as per the psychological mindset of the students in the class. The main focus is to take advantage of a high population with rich cultural strength and not to divert attention to the problems which are associated with the high population. The different stakeholders must have to come up with synchronized policies with an approved law where everyone person of India has opportunities to explore their true potential and ultimately give a contribution to the development of Indian society. The rich cultural strength must be utilized with a positive mindset. Despite the high student-teacher ratio, ample opportunities must be created by the teachers to enrich the classroom with good classroom practices. The outcome of the study confirms that the rich cultural differences provide opportunities for the students to explore their true potential as well as provide a challenging platform for the teachers to act upon the new strategies for the development of the students as well as the for the development of Indian society.